(untitled) (Research, Society and Development, 2023)
The use of carboxytherapy has shown excellent results in the treatment of various aesthetic conditions. The aim of this study was to investigate the effects of carboxytherapy on cellulite and striae distensae (SD). Therefore, a systematic literature review was accomplished on two databases, Medline via PubMed and Scopus, from July to August 2021. Studies that evaluated the effect of carboxytherapy on SD and cellulite were included, eight articles of all of them and that treated 299 people were included in this systematic review and the most studies classified as having low level of methodological quality. There was no consensus regarding the parameters used, but in most studies and applications were performed at a depth of 10 mm with a flow ranging from 50 to 150 mL / min. The results this intervention produced an improvement in skin aspects, with better texture, decreased severity of cellulite and SD, improved patient satisfaction, increased skin thickness, decreased edema and increased inflammatory infiltrate the number of collagen fibers. Some side effects were observed, such as transient erythema and post-inflammatory hyperpigmentation, leading to discomfort. However, all these adverse effects are transient, and patients can return to normal activities with the use of photoprotection. This review demonstrates the stimulatory effect of carboxytherapy on the symptomatology of patients with cellulite and SD.